Estudo fitoquímico e avaliação do potencial antimicrobiano de espécies de Hortia (Rutaceae) : H. oreadica, H. brasiliana e H. superba - Severino, Vanessa Gisele Pasqualotto (2008)
The phytochemical study of Hortia in this work aims to contribute with the chemosystematics of the Rutaceae and with the best classification of the genus inside the family. The study of the species H. oreadica, H. brasiliana and H. superba led us to isolate 15 compounds, such as the dihydrocinnamic acids derivatives 3-phenyl-[2 ,6 -dimethoxy-(3 ,4 :5 ,6 )-2 ,2 - dimethylpirano]propionic acid (01), methyl 3-phenyl-[2 -methoxy-(3 ,4 :5 ,6 )-2 ,2 - dimethylpirano]propionate (02), methyl 3-phenyl-[2 ,6 -dimethoxy-(3 ,4 :5 ,6 )- 2 ,2 -dimethylpirano]propionate (03), methyl 3-phenyl-[2 ,5 -dimethoxy- (3 ,4 :5 ,6 )-2 ,2 -dimethylpirano]propionate (04), 3-phenyl-[2 -methoxy- (3 ,4 :5 ,6 )-2 ,2 -dimethylpirano]propionic acid (05), 3-phenyl-[2 ,5 -dimethoxy-(3 , 4 -O:5 ,6 ) 2 ,2 -dimethylpyrano]propionic acid (06), being structure 06 new for specie H. oreadica; coumarin 5-methoxyseselin (07); cinnamic acid derivative E- 3,4-dimethoxy-á(3-hydroxy-4-carbomethoxyphenyl)cinnamic acid (08), new in literature, the alkaloids rutaecarpine (09), 7,8-dehydrorutaecarpine (10) new in the genus Hortia, dictamine (11), N-methylflindersine (12) and the limonoids guyanin (13), hortiolide E (14) and hortiolide G (15), being structure 14 described for the first time in the specie H. oreadica and 15 in literature. The phytochemical study of the species from Hortia genus still not allow classify correctly it inside the family. Hortia presents limonoids with C and D rings modified, characteristic of Meliaceae. However the presence of metabolites such as alkaloids, coumarins, dihydrocinnamic and cinnamic acids derivatives confirm that Hortia belongs the Rutaceae family, even so are not clear its accurate positioning. The presence of limonoids highly modified could indicated that genus can not belong nor to the Todallieae and nor the Cusparieae, being located separately inside of the Rutaceae family. Several biological assays had been performed with crude extracts and compounds isolated from Hortia, with a collection of the synthetic compounds and the lasiodiplodin, compound isolated from the pathogenic fungus. The Minimum Inhibitory Concentration of many substances was related against the bacteria Xylella fastidiosa that causes Citrus Variegated Chlorosis. The promising substances were synthetic quinolinones 2-methyl-6-fluor-4-quinolone (S2) and 2-methyl-5-methoxy-7-hydroxy-4-quinolone (S4) and the alkaloid rutaecarpine (09) with MIC from 0.5 to 1.0 mg/mL. We have studied the in vitro antimicrobial activity against oral pathogens that permitted to determine hexane extract such as successful against all microorganisms assayed and limonoid guyanin (13) and alkaloid dictamine (11) with the best MIC, being 200 and 100 µg/mL, respectively. The assays against alimentary pathogens revealed that lasiodiplodin, 2-methyl-6-fluor-4-quinolone (S2) and 2-methyl-5,7-dimethoxy-4- quinolone (S4) synthetics as the more effective among all substances. Therefore, this work showed that several substances with properties antibacterial constitute an important source for the discovery of new antimicrobial products.